Global audiences, local images: The question of exoticization in Slumdog Millionaire - Lamsal, Tika (Bodhi: An Interdisciplinary Journal, 2012)
DOI: http://dx.doi.org/10.3126/bodhi.v4i1.5820 Bodhi 2010 4(1): 198-209